Neuromodulation Effect of Very Low Intensity Transcranial Ultrasound Stimulation on Multiple Nuclei in Rat Brain - Liu, Yingjian; Wang, Gang; Cao, Chao; Zhang, Gaorui; Tanzi, Emily B.; Zhang, Yang; Zhou, Weidong; Li, Yi (Frontiers in Aging Neuroscience, 2021)
objective: Low-intensity transcranial ultrasound stimulation (TUS) is a non-invasive neuromodulation technique with high spatial resolution and feasible penetration depth. To date, the mechanisms of TUS modulated neural oscillations are not fully understood. This study designed a very low acoustic intensity (AI) TUS system that produces considerably reduced AI Ultrasound pulses (ISPTA< 0.5 W/cm2) when compared to previous methods used to measure regional neural oscillation patterns under different TUS parameters. Methods: We recorded the local field potential (LFP) of 5 brain nuclei under TUS with 3 groups of simulating parameters. Spectrum estimation, time-frequency analysis (TFA), and relative power analysis methods have been applied to investigate neural oscillation patterns under different stimulation parameters. Results: Under PRF, 500 Hz and 1kHz TUS, high-amplitude LFP activity with the auto-rhythmic pattern appeared in selected nuclei when ISPTA exceeded 12 mW/cm2. With TFA, high-frequency energy (slow gamma and high gamma) was significantly increased during the auto-rhythmic patterns. We observed an initial plateau in nuclei response when ISPTA reached 16.4 mW/cm2 for RPF 500Hz and 20.8 mW/cm2 for RPF 1kHz,. The number of responding nuclei started decreasing while ISPTA continued increasing. Under 1.5 kHz TUS, no auto-rhythmic patterns have been observed, but slow frequency power was increased during TUS. TUS inhibited most of the frequency band and generated obvious slow waves (theta and delta band) when stimulated at RPF= 1.5kHz, ISPTA =8.8 mW/cm2. Conclusion: These results demonstrate that very low intensity Transcranial Ultrasound Stimulation (VLTUS) exerts significant neuromodulator effects under specific parameters in rat models and may be a valid tool to study neuronal physiology.